Penggunaan Tiktok Pada Mahasantri Ma’had Al Jamiah UINSU Tinjauan Aspek Etika Komunikasi Islam - Sarmila Haerani Siregar; Ahmad Tamrin Sikumbang (STAI Bumi Silampari, 2025)
The rapid development of social media, especially TikTok, has had a significant influence on communication ethics, including among students of Ma'had Aljamiah UINSU. TikTok as a popular platform allows instant exchange of information, but often ignores Islamic communication values. This study aims to examine the use of TikTok by students from the perspective of Islamic communication ethics. The method used is descriptive qualitative with a single case study approach. Data were obtained through interviews, observations, documentation, and content analysis. The results of the study show that although social media is often filled with impolite or controversial communication, students still try to maintain Islamic communication principles in every interaction. They prioritize friendly and positive communication, verify information (Tabayyun), and avoid harsh words and maintain peace in communication (Silm). Interviews with students showed that they were aware of the importance of filtering information and maintaining speaking ethics, even amidst the dominance of negative trends on social media. These principles are not only guidelines for preaching, but also as steps to maintain constructive and peaceful communication in the digital space